Why is Mouth Self-Examination Still Not Recommended for Early Detection of Oral Cancer and Oral Potentially Malignant Disorders? - Beatriz Monteiro da Silva; José Alexandre da Rocha Curvelo; Ruteléia dos Santos Assumpção Barroso; João Vitor Silveira de Azevedo; Andreia Cristina de Melo; Daniel Cohen-Goldemberg (Revista Brasileira de Cancerologia)
Oral self-examination still remains enigmatic considering its functionality in detecting malignant disorders in the mouth. Although this tool is not concretely implemented in any health service, several studies have considered it as a real possibility for the screening and the early diagnosis of oral cancer. However, the heterogeneity of the methodologies applied in these studies makes their results inconsistent and imprecise, making the validation of oral self-examination impossible to date. Thus, once the methodological issues that compromise the real efficacy of self-examination have been resolved, this tool should be used and perhaps be considered essential as a strategy to detect malignant lesions, contributing to more favorable outcomes for oral cancer in public health.